The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/ene.12411
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide predicts stroke of presumable cardioembolic origin in addition to coronary artery calcification

Abstract: BNP predicts presumable cardioembolic stroke independent of coronary calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Moreover, BNP is increased in subjects with early stages of cardiac diseases such as diastolic dysfunction and left ventricular hypertrophy which also are associated with AF [7,8]. In population-based studies, BNP predicted major cardiovascular outcomes in subjects without known cardiac diseases [9,10]. However, data on the ability of BNP to predict future AF based on general population cohorts are limited.…”
mentioning
confidence: 99%
“…Moreover, BNP is increased in subjects with early stages of cardiac diseases such as diastolic dysfunction and left ventricular hypertrophy which also are associated with AF [7,8]. In population-based studies, BNP predicted major cardiovascular outcomes in subjects without known cardiac diseases [9,10]. However, data on the ability of BNP to predict future AF based on general population cohorts are limited.…”
mentioning
confidence: 99%
“…Different applications have been assigned to N‐terminal section brain natriuretic peptide (NT‐proBNP) in several studies, and an acceptable diagnostic value in distinguishing ischemic stroke from other subtypes (Hajsadeghi et al, ) also predicts presumable cardioembolic stroke independent of coronary calcification (Kara et al, ; Yang et al, ). Moreover, it is a significant predictor of major adverse cardiovascular events in stable coronary disease, as well as a strong predictor of death and a wide range of cardiovascular events (Linssen et al, ; Mishra et al, ) and some non‐cardiovascular causes (Oluleye et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Kara et al, 3 BNP predicted stroke in men but not in women, both in subjects under and over 65 years of age. In another study by Duschek et al, 4 the authors assessed NT-proBNP in both men and women with asymptomatic high-grade carotid stenosis, and concluded that male patients ≥75 years with low levels of NT-proBNP had the same survival rate as younger patients, making them eligible for carotid endarterectomy.…”
mentioning
confidence: 97%